Single non healing digital ulcer. An unusual presentation of leprosy. - Bhalla, N.; Someshwar, S.; Jerajani, H.; Bhatt, K.D. (European Journal of Pediatric Dermatology, 2014)
Leprosy has been identified as an important health problem in the pediatric age group in India. The study of leprosy in children is imperative as it may unravel the missing links in the natural evolution of the disease. Unusual presentations of leprosy pose great challenges in diagnosis and hence are a reason for the delay in treatment. Here we a report a case of a 15-year-old child who presented to us with a single non healing digital ulcer.